Pengembangan Bahan Ajar Fisika Berbasis Somatic, Auditory, Visual, Intellectual (SAVI) untuk Meningkatkan Keterampilan Berfikir Kritis Siswa - Iman Darmawan; M. Nuzuluddin; Hadian Madala Putra; Suhartini Suhartini (Universitas Hamzanwadi, 2022)
This study aims to develop an SAVI-based physics teaching module with appropriate scientific content to improve students' critical thinking skills. This research is a research and development research. The module development model used is a 4D model (four D model). The four stages are Define, Design, Development and Disseminate proposed by Thiagarajan. The development of this module is assessed based on the feasibility of the content, presentation, and language of the module and then tested on students. After being revised, the module was then tested in the science class. Collecting data in this study using test questions. The result of this research is that the SAVI-based physics teaching module to improve students' critical thinking skills has the characteristics that the SAVI-based Physics Module is developed using the SAVI learning stage, including the preparation stage, delivery stage, training stage, and result performance stage as well as, integrating critical thinking skills in each lesson. steps and contains critical thinking test questions. The SAVI-based physics teaching module is suitable for use as teaching material based on the results of the main field trial, the results obtained that 86% of students stated that this module was in very good criteria for module readability from the aspects of material, media, and language.